2021
DOI: 10.3233/idt-200038
|View full text |Cite
|
Sign up to set email alerts
|

An innovative method for cardiovascular disease detection based on nonlinear geometric features and feature reduction combination

Abstract: Cardiovascular is arguably the most dominant death cause in the world. Heart functionality can be measured in various ways. Heart sounds are usually inspected in these experiments as they can unveil a variety of heart related diseases. This study tackles the lack of reliable models and high training times on a publicly available dataset. The heart sound set is provided by Physionet consisting of 3153 recordings, from which five seconds were fixed to evaluate to the developed method. In this work, we propose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Sun et al studied the classroom comprehensive evaluation from the mathematical model, the classification of mathematics teaching contents, and mathematics exercises after class and adopted different teaching strategies for experimental teaching [ 12 ]. Saeedi et al showed that the teaching method has good stability in improving the quality of mathematics teaching and is suitable for the formulation of the optimal teaching plan [ 13 ]. In order to improve the teaching efficiency and overall stability of mathematics teaching classroom, through the research and analysis of different students, a hierarchical teaching method is proposed based on mathematics teaching theory [ 14 ].…”
Section: Related Workmentioning
confidence: 99%
“…Sun et al studied the classroom comprehensive evaluation from the mathematical model, the classification of mathematics teaching contents, and mathematics exercises after class and adopted different teaching strategies for experimental teaching [ 12 ]. Saeedi et al showed that the teaching method has good stability in improving the quality of mathematics teaching and is suitable for the formulation of the optimal teaching plan [ 13 ]. In order to improve the teaching efficiency and overall stability of mathematics teaching classroom, through the research and analysis of different students, a hierarchical teaching method is proposed based on mathematics teaching theory [ 14 ].…”
Section: Related Workmentioning
confidence: 99%